Serum-Free Culture System for Spontaneous Human Mesenchymal Stem Cell Spheroid Formation - Guoyi Dong; Shengpeng Wang; Yuping Ge; Qiuting Deng; Qi Cao; Quanlei Wang; Zhouchun Shang; Wenjie OuYang; Jing Li; Chao Liu; Jie Tang; Weihua Zhao; et al. (Stem Cells International)
Human mesenchymal stem cells (hMSCs) are widely used in clinical research because of their multipotential, immunomodulatory, and reparative properties. Previous studies determined that hMSC spheroids from a three-dimensional (3D) culture possess higher therapeutic efficacy than conventional hMSCs from a monolayer (2D) culture. To date, various 3D culture methods have been developed to form hMSC spheroids but most of them used culture medium containing fetal bovine serum (FBS), which is not suitable for further clinical use. Here, we demonstrate that dissociated single MSCs seeded in induced pluripotent stem medium (MiPS) adhere loosely to the dish and spontaneously migrate to form spheroids during day 3 to day 6. Through component deletion screening and complementation experiments, the knockout serum replacement (KSR) was identified as necessary and sufficient for hMSC spheroid formation. Transcriptome analysis showed that the overall expression profiles were highly similar between 2D culture with FBS and KSR-derived spheroids. Interestingly, genes related to inflammatory response, immune response, and angiogenesis were upregulated in spheroids at day 6 and qPCR results further validated the increased expression level of related genes, including STC1, CCL7, HGF, IL24, and TGFB3. When spheroids were replated in normal FBS medium, cells formed a typical spindle-shaped morphology and FACS results showed that the recovered cells retained MSC-specific surface markers, such as CD73, CD90, and CD105. In summary, we developed a practical and convenient method to generate hMSC spheroids for clinical research and therapy.